Aplikasi Inventory dengan Visualisasi Penjualan Berbasis Outflow Stok pada Toko Ritel - Dzulfikar, Muhamad Althaf Atsaqif; Asriningtias, Yuli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Inventory management in retail stores often faces constraints regarding recording accuracy, restocking delays, and difficulties in preparing reports when processes are still carried out manually. This research designs and implements a mobile-based inventory application in a Retail Store case study to handle login–register authentication, mapping of item storage locations, management of categories and item data, recording of in-out transactions (not POS/cashier), sales visualization based on item outflow in bar diagrams, and periodic reports of incoming and outgoing goods. The development methodology applied is Black-box Functional Testing on core scenarios. Black-box functional testing on 9 core scenarios achieved a 100% success rate, covering login–registration, master data management, incoming–outgoing transactions, stock-outflow visualization, and report export. The system architecture adopts Flutter on the client side, Node.js–Express on the service side, and MySQL on the database side. The development methodology is iterative, covering requirements elicitation, data model design with ERD and process flow with DFD, module implementation, and black-box functional testing on core scenarios. The implementation results demonstrate that all modules operate according to specifications: transactions automatically update stock, visualization highlights best-selling products through stock outflow indicators, and period reports support restocking decisions. These findings affirm that the application successfully enhances operational efficiency and employee productivity due to faster and easier recording, mitigates the risk of item data loss, and provides accurate analysis regarding stock outflow that aids in predicting and optimizing restocking policies.